AESTHETIC EDUCATION OF THE FUTURE SPECIALIST IN HIGHER EDUCATION INSTITUTIONS BASED ON THE TOOLS OF APPLIED FOLK ART - Matkarimov , Azamat Farhod o‘g‘li (Innovative Development in Educational Activities, 2023)
The article examines the essence of the category of aesthetic subjective position of a person, the general teacher as an integral part of his aesthetic culture, the main conditions of its formation are considered, the system of development of aesthetic culture in the university, in which the subjective position is developed.